COMPLIANCE: ESSENCE, INTERNATIONAL STANDARDS AND PROSPECTS OF DEVELOPMENT FOR UKRAINIAN BANKS - PRYMOSTKA, Liudmyla; KRASNOVA, Iryna; STRILCHUK, Yuliia (Herald of Khmelnytskyi National University. Economic sciences, 2025)
Compliance with the law is crucial to prevent legal, financial, and reputational risks, especially in the digital age. Ukrainian banks are looking for effective tools to develop compliance management systems. The theoretical generalisation enabled identifying the following approaches to understanding the essence of ‘compliance’: systemic, process, value, and functional. The presented approaches form a comprehensive understanding of the essence of the ‘compliance in a bank’ concept. An analytical review of international regulatory documents on the basics of integrity is carried out. The key principles of compliance management are highlighted in the Basel Recommendations. These principles define the basis for the activities of the compliance unit and establish the most important principles for introducing the compliance function into corporate banking governance practices. In the context of European integration, international standards should become an integral part of compliance management development in all Ukrainian banks. The review of the international standards and guidelines allowed us to determine the prospects for the development of compliance management in Ukrainian banks. The development of compliance management in a bank should be based on a system of norms, rules, requirements, and standards set out in the relevant internal documents in written form and approved by the authorised departments. Interaction between employees, managers, top executives, and owners should be based on practice-oriented standards and rules. The key role of compliance procedures in internal conflicts is to minimise ‘grey areas’ and to protect the rights and interests of each party of the conflict. The bank should become a reliable partner and a space where stakeholders can achieve other important economic and/or social effects through synergy. Banks should prevent the achievement of criminal goals and counteract cash flows that may violate the rules of other areas of legislation.  The formation of a compliance mindset among the population and the introduction of a compliance strategy into the bank's corporate governance should become long-term trends in the development of effective compliance management systems.
Keywords: compliance management; bank; corporate governance; banking activities; regulation; risk management; ethical behaviour; monitoring; digital transformation; European integration; financial literacy; crime prevention